Comparison of Improvement in 2-Year Survival Rate of Patients with Stage II-III Non-Small Cell Lung Cancer Treated with Different Durations of Chinese Patent Medicine: A Retrospective Cohort Study - Wang, Li; Jia, Kegang; Li, Fang; Zhang, Chenxu; Feng, Gang; Du, Jun (Frontiers in Pharmacology, 2021)
Background: Chinese patent medicine is widely used in patients with malignant tumors, and current studies have shown that long-term treatment with Chinese patent medicine is related to the improvement of the outcome of patients with malignant tumors. This retrospective study was conducted to preliminarily explain the effect of different duration of treatment with Chinese patent medicine and Huisheng oral liquid on 2-year survival rate, and to explore prognostic factors affecting 2-year survival rate of patients. Purpose: To compare the effect of different duration of treatment with Chinese patent medicine and Huisheng oral liquid on 2-year survival rate of patients with stage II-III NSCLC, and explore the prognostic factors of 2-year survival rate. Methods: Kaplan-Meier method was used to compare the 2-year survival rate of patients treated with different duration of Chinese medicine and Huisheng oral Liquid. The relationship between different treatment duration and improvement of 2-year survival rate was explored by Cochran-Armitage trend test. Cox proportional hazards regression models were used to explore factors affecting 2-year survival rate of patients. Results: A total of 614 patients with stage II-III NSCLC diagnosed from January 2015 to December 2018 were included in this study.The results showed that: ①The 2-year survival rate of patients treated with Chinese patent medicine for ≥ 3 months and ≥ 6 months was higher than that of patients treated < 3 months. ②The 2-year survival rate of patients treated with Huisheng Oral Liquid for ≥ 3 months was higher than that of patients treated for < 3 months. Cochran-Armitage trend test showed that the 2-year survival rate tended to increase with the duration of Huisheng Oral Liquid treatment. ③ Cox proportional hazards regression model revealed that surgery, chemotherapy and Huisheng Oral Liquid ≥ 3 months were protective factors; Gender was male and FIB ≥ 4g/L were risk factors. Conclusion: Chinese patent medicine and Huisheng oral liquid treatment for ≥ 3 months showed an improvement in 2-year survival rate of patients with stage II-III NSCLC. 2-year survival rate tended to increase with the treatment duration. Finally, the gender was male and FIB ≥ 4g/L were risk factors for prognosis.